Understanding True Religion as Ethical Knowledge - Afifi, Abdullah A (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2021)
Hatred, extremism, terrorism and islamophobia become challenges for religion nowadays. The weight of this issue burdens the understanding of society about religion. Either to be a secular atheist or alienated religious extremist are not an appropriate solution. Alternatively, an approach needed to define religion as the source of ethical knowledge and facilitated the construction of new tolerance that not exclude the religion from people’s affair. This paper discusses the true religion and how they construct ethical knowledge used for the development of civilization.